2017
DOI: 10.1037/scp0000144
|View full text |Cite
|
Sign up to set email alerts
|

From defiance to reliance: Spiritual virtue as a pathway towards desistence, humility, and recovery among juvenile offenders.

Abstract: This study examined the impact of two “spiritual virtues”—service to others and the spiritual experience of love—on sobriety, character development (humility), and recidivism. We control for conduct disorder and other comorbid conditions, including defiant behaviors. One hundred ninety-five adolescents with substance dependency court-referred to residential treatment were assessed at intake, discharge, and 12 months posttreatment. Higher service to others predicted reduced relapse and greater humility, with or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…Evidence-based studies have found that youths who are spiritually active, participate in a faith community, and invest in a prayerful relationship with their God are less likely to use or abuse drugs and alcohol and engage in related criminal activity (Johnson et al 2015, 2016a, b; Lee et al 2014, 2017; Post et al 2015, 2016). A seminal 2-year study by The National Center on Addiction and Substance Abuse (2001) at Columbia University, directed by Joseph A. Califano Jr., the former US Secretary of Health, Education, and Welfare in the Clinton administration, found that the teens who did not consider religious beliefs important were almost three times more likely to smoke, five times more likely to binge on alcohol, and almost eight times more likely to use marijuana compared with the teens who strongly appreciated the significance of religion in their daily lives.…”
Section: Sections Of the Studymentioning
confidence: 99%
“…Evidence-based studies have found that youths who are spiritually active, participate in a faith community, and invest in a prayerful relationship with their God are less likely to use or abuse drugs and alcohol and engage in related criminal activity (Johnson et al 2015, 2016a, b; Lee et al 2014, 2017; Post et al 2015, 2016). A seminal 2-year study by The National Center on Addiction and Substance Abuse (2001) at Columbia University, directed by Joseph A. Califano Jr., the former US Secretary of Health, Education, and Welfare in the Clinton administration, found that the teens who did not consider religious beliefs important were almost three times more likely to smoke, five times more likely to binge on alcohol, and almost eight times more likely to use marijuana compared with the teens who strongly appreciated the significance of religion in their daily lives.…”
Section: Sections Of the Studymentioning
confidence: 99%
“…The recurring or common attributes observed in the previous section are also summarized in several publications:22,35,38,43 Accurate assessment of one’s abilities and achievements; ability to acknowledge one’s mistakes, imperfections, gaps in knowledge, and limitations; openness to new ideas, contradictory information and advice, teachability; keeping one’s abilities and accomplishments in perspective; modest social portrayal of self as a part of the larger universe; appreciation of the value of all things, as well as the many different ways that people and things can contribute to our world; other-oriented rather than self-focused thinking; with respect to self-preservation in a competitive society (finances, pride, recognition), people with humility are more generous by giving accolades and benefits to others; lack of entitlement and willingness to work hard to earn by achievement. A study of social relationship quality reported a positive correlation between a revised Quality Marriage Index and the HEXACO humility score in college students 44…”
Section: Analysesmentioning
confidence: 83%
“…Krause’s definition of humility may appear detrimental to enhancing interdisciplinary collaboration; however, other researchers explain (spiritual) humility differently. Fostering greater humility is considered a part of character development for juvenile offenders, and the act of helping others flows from a spiritually grounded humility 22. Lee et al (2017) viewed the treatment of addictive behaviors through the spiritual virtues of humility and altruism.…”
Section: Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…This experience combined with high levels of service to others produced higher levels of humility and was associated with reduced one-year recidivism and relapse rates. 42 Adolescents with severe SUD and those with comorbid psychiatric problems participate in 12-step groups at similar or higher levels and experience comparable or better outcomes than their less severely affected counterparts. 43,7 Moreover, 12-step involvement by adolescents has been shown to reduce medical costs over a 7-year period after treatment, with an estimated cost reduction ratio of 4.7% for every 12-step meeting attended.…”
Section: Introductionmentioning
confidence: 99%